Effect of effluent recirculation on nutrients and organics removal performance of hybrid constructed wetlands: Landfill leachate treatment. (1st February 2021) - Saeed, Tanveer; Miah, Md Jihad; Majed, Nehreen; Alam, Md Kawser; Khan, Tanbir
Abstract: Landfill leachate treatment is challenging because of complex chemical composition. This study identifies the factors associated with organics and nutrients removal performance improvement in construction or organic materials based four hybrid wetland systems dosed with landfill leachate. The imbalanced pollutant composition ratio of leachate influenced removal pathways in the hybrid wetlands; effluent recirculation (50 and 25% ratios) adjusted leachate composition and improved removal performances. Mean nitrogen (N), phosphorus (P), biochemical oxygen demand (BOD), and chemical oxygen demand (COD) removal percentages in the hybrid wetlands during without, with recirculation periods ranged between 50 and 93, 69–100, 34–89, and 55–76%, respectively. Pollutant removals were achieved through adsorption, microbial (heterotrophic organic removal, ammonia assimilation, nitrification, denitrification) degradation, and plant uptake. Removal rates did not vary substantially among organic or construction materials based first stage VF (vertical flow) wetlands because of leachate composition. Constant water saturation depth variation influenced pollutant removal rates among the second stage wetlands. Shallow water depth HF (horizontal flow) wetlands appeared to be a promising wastewater treatment technology due to the coexistence of unsaturated, saturated bed matrix that supported diverse removal pathways. Graphical abstract: Image 1 Highlights: Effluent recirculation improved the leachate biodegradation ratio. Ammonia assimilation, ammonification, nitrification, denitrification removed N. Media supported nutrient adsorption. Shallow water depth HF wetlands supported concurrent aerobic-anaerobic removals.